Interactive Emergency TeleHealth Systems in Pandemic Times: a Usability Evaluation in the Interior of Brazil - Capeleti, Bruna Santana; Dominguete, Gustavo Lopes; Pereira, Marluce Rodrigues; Freire, André Pimenta (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2021: Anais do XX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2021)
With the emergence of the COVID-19 pandemic, people had to avoid crowded places and attend hospitals, clinics, and doctors' offices only in an emergency. The authors' institution developed a telehealth platform prototype in a joint effort between Health and Computer Science researchers and students to allow the participation of medical students under the supervision of medical professors to provide emergency health advice using online remote care supported by a video and form-filling tool to support in preliminary diagnosis. This paper presents a usability evaluation of the telehealth platform prototype involving 30 participants in a medium-sized town in the interior of Brazil. Participants simulated virtual consultations about COVID-19 with health professionals. The usability evaluations were fundamental to understanding users' mental models, how to provide a better experience and measuring the system's effectiveness and acceptance. The findings show implications to the design of telehealth systems and the impact of problems related to Information Architecture, user feedback, controlling video-based interfaces. The preliminary results encountered in the present study are essential to help improve the usability of telehealth solutions, which will have a significant growth following the trend from the COVID-19 pandemic.